The Effect of Berry‐Based Food Interventions on Markers of Cardiovascular and Metabolic Health: A Systematic Review of Randomized Controlled Trials. Issue 1 (10th January 2018) - Heneghan, Clara; Kiely, Mairead; Lyons, Jacqueline; Lucey, Alice
Abstract : Scope: Epidemiological evidence, animal, and in vitro studies suggest that berry consumption may ameliorate markers of cardiovascular disease (CVD). The aim of this systematic review is to evaluate findings from berry‐based randomized controlled trials (RCTs) to establish the effects of berry consumption on markers of cardiovascular and metabolic health. Methods and results: PubMed and Web of Science are searched for RCTs investigating berry consumption on CVD risk outcomes in adults. A total of 23 studies (which includes 1168 participants) out of 1384 records meet the inclusion criteria. Of these 23 studies, 17 RCTs are of high quality, where 12 RCTs (71%) report beneficial effects of berry consumption on CVD risk markers. Overall, 4/11 RCTs that observe a reduction in systolic and/or diastolic blood pressure (BP); 3/7 RCTs report favorable effects on endothelial function, 2/3 RCTs report improvements in arterial stiffness, 7/17 studies observe benefits in blood lipids, and 3/6 studies report improvements in glycemic profile. Conclusion: Our evaluation of the literature indicates that more than two‐thirds of high‐quality trials have reported beneficial effects of berry consumption on markers of CVD risk. This systematic review contributes moderate to strong evidence for the inclusion of berries as part of a cardioprotective diet. Abstract : Berries may reduce the risk of cardiovascular disease (CVD) through the amelioration of CVD risk factors such as blood pressure, lipid profile, vascular endothelial function, arterial stiffness and glycemic profile. A systematic review was undertaken to evaluate the findings from berry‐based randomized controlled trials (RCTs) on CVD risk. Findings from this review reinforce the need for the promotion of berry consumption as part of a cardioprotective diet and also make a contribution to the design of future novel berry‐based foods with functional health outcomes.